Evaluation of bio-formulations for management of storage rot of seed tubers of Colocasia (Colocasia esculenta) (Current Horticulture, 2024)
The seed tubers of Colocasia (Colocasia esculenta L.) collected from different locations were treated with several bio-formulations, viz. Biofor PF-2, Biomonas, Bioveer and Biozin PTB at 5% concentration to evaluate their efficacy in protecting the seed tubers from rotting in storage. Biozin PTB was found to be the most effective with lowest incidence (8.84%) of rot among all bio-formulations. The seed tubers treated with Biozin PTB recorded highest reduction (80.94%) of rot incidence over the control.
Keywords: Bio-formulations; Cormlets; Rot incidence; Seed tubers; Storage rot